Facile room-temperature synthesis of highly air‐stable and moisture-resistant CsPbX3/SiO2 nanocomposites for tunable white light-emitting diodes. (December 2021) - Chao, Li-Wei; Tang, Jian-Fu; Lin, Shih-Hung; Lee, Yi-Ting; Chen, Yi-Lun; Hsieh, Cheng-Ho; Chen, Lung-Chien; Tseng, Zong-Liang
Abstract: All inorganic perovskite quantum dots (PQDs) and perovskite CsPbX3 /SiO2 nanocomposites (PNCs) have shown their potentials for optical and lighting applications. We demonstrate a one-step approach to synthesize PQDs and PNCs more simply and effectively at room temperature in the open air. The resulting PNCs can show a narrow emission in the PL spectra and high stability under ambient conditions. In particular, both green CsPbBr3 /SiO2 and red CsPbI3-x Brx /SiO2 PNCs can be obtained by employing this easy and low-cost method. Even, the SiO2 protection can also effectively prevent the halide exchange reaction between green and red PNCs, meaning the capability for white light applications. The resulting white light-emitting diodes (WLEDs) based on the green and red PNCs coated on the blue LED have a white Commission Internationale del' Enclairage (CIE) coordinates of (0.375, 0.362) and a low correlated color temperature (CCT) of 4054 K.